Financial literacy – best practices - Colić, Vana (Norma, 2022)
The most commonly accepted definition of financial literacy is the one given by the OECD, which includes awareness, knowledge, skills, attitudes, and behaviours. The concept of financial literacy must be distinguished from the concepts of financial education, financial knowledge, and financial culture. The research results show that financial illiteracy is widespread, and it is generally necessary to pay more attention to this aspect of education. After defining the basic concepts, the paper presents experiences in organizing and monitoring the effects of financial education of three countries (Estonia, Finland, the Netherlands) whose students have achieved a high level of financial knowledge in international tests compared to other participating countries. The organisation of financial education in these countries is also presented, in order to assess how applicable their experiences are in our conditions. The experience thus far has shown that the best results are given by financial education beginning in high school, whose main characteristics are an interdisciplinary approach and constant support to teachers. Significant differences are also evident, that is to say, some groups of residents have a lower level of financial literacy, which indicates the need for different approaches in their education.